Tri Hita Karana Memoderasi Sistem Pengendalian Internal dan GCG pada Kinerja Lembaga Perkreditan Desa - Astini, Ni Putu Ayu; Utama, I Made Karya (E-Jurnal Akuntansi, 2023)
Problematic LPDs are generally identified by their poor financial performance. LPD's financial performance is seen from the effectiveness of implementing the internal control system, GCG, and tri hita karana within the organization. This research aims to analyze the influence of internal control and GCG on LPD performance with tri hita karana as moderation. The population of this study is all LPDs in Mendoyo District with a total of 19 LPDs. The sampling technique used is purposive sampling with the criteria that the LPD is still active, gives permission for research to be carried out, and has an internal control system, GCG, and tri hita karana in managing the LPD. Data collection took the form of a questionnaire, analyzed using Moderated Regression Analysis (MRA) using SPSS. The results of this research show that the internal control system and GCG have a positive effect on the financial performance of LPDs in Mendoyo District, and are moderated (strengthened) by tri hita karana. The implications of this research can be input for the LPD to improve and consider it in decision making. Keywords: Internal control system; GCG; tri hita karana; financial performance; LPD.